1997
DOI: 10.1016/s0035-9203(97)90521-6
|View full text |Cite
|
Sign up to set email alerts
|

Wuchereria bancrofti microfilaraemia in children in relation to parental infection status

Abstract: A total of 946 families with 2302 children was surveyed for microfilaraemia due to Wuchereria bancrofti. The prevalence of microfilaraemia among offspring born to microfilaraemic parents was significantly higher than in those born to amicrofilaraemic parents (P = 0.0049; relative risk = 3.40). However, there was no statistically significant difference between the prevalence of microfilaraemia in children born to microfilaraemic mothers or microfilaraemic fathers, suggesting that parental (not only maternal) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
3
8
1
Order By: Relevance
“…As in prior studies, we have no information on the infection status of mothers during gestation, but we assume that many of the women who were infected at the time of our study were also infected during their pregnancies. Our results are similar to those recently reported by Alexander and others 21 and by Das and others 22 in that infection in either parent was associated with a significantly increased risk of infection in children, and there was no special risk associated with maternal infection. Unlike Alexander and others, we found that the risk associated with parental infection was independent of village of residence, but this does not exclude the possibility that the association was caused by environmental factors affecting exposure to infection that are shared between parents and children residing in the same houses.…”
Section: Discussionsupporting
confidence: 92%
“…As in prior studies, we have no information on the infection status of mothers during gestation, but we assume that many of the women who were infected at the time of our study were also infected during their pregnancies. Our results are similar to those recently reported by Alexander and others 21 and by Das and others 22 in that infection in either parent was associated with a significantly increased risk of infection in children, and there was no special risk associated with maternal infection. Unlike Alexander and others, we found that the risk associated with parental infection was independent of village of residence, but this does not exclude the possibility that the association was caused by environmental factors affecting exposure to infection that are shared between parents and children residing in the same houses.…”
Section: Discussionsupporting
confidence: 92%
“…Meyrowitsch et al (1995a) demonstrated that individual micro® larial positivity remained remarkably static for 16 years in a Tanzanian community. In contrast to the present results, Das et al (1997), working in India, did not observe any signi® cant difference in the prevalence of micro® laraemia between children born to micro® laraemic mothers and those born to micro® laraemic fathers, and they suggested that intra-familial exposure to W. bancrofti was more important than inborn tolerance to the parasite.…”
Section: Discussioncontrasting
confidence: 99%
“…13 Other studies have indicated that children of both mf-positive mothers and fathers are more likely to be mf positive than children of mf-negative parents. 37,38 Based on these studies, it appears that parental and not only maternal infection is the more important risk for infection in the offspring, probably due to increased household exposure. The present study analyzed the relationship between infection status of parents and that of their children not only for mf, but also for the first time for CFA.…”
Section: Discussionmentioning
confidence: 98%